Instituições e crescimento econômico de longo prazo : uma análise em painel espacial com ênfase na América Latina e Caribe no período de 1975-2016 - Almeida, Sivanildo José de (2020)
: The modern theory of economic growth has identified several factors as being crucial to the good performance of countries, among which are: physical / human capital, technological progress, government spending, trade opening, among others. However, alternative theories present other components as fundamental to the economic growth of nations, this is the case of institutionalist theory, which reinforces the role of institutions and which has been widely disseminated, especially since the 1990s. The definition of institution used in this work is by Douglass North, for him, institutions are restrictions that guide people's behavior, resulting in the improvement of the coexistence of the whole society. Institutions can be formal (rules, laws and constitution) and informal (codes of conduct and culture of a society). For this theoretical aspect, the key to understanding the economic growth of different countries over time, lies in the study of the dynamics and institutional change of economies. Thus, the objective of the work is to analyze the influence of the institutional environment on the economic growth of the countries, with an emphasis on Latin America and the Caribbean, from the perspective of the New Institutional Economy (NIE), aiming to identify the role of institutions in growth differences. The period analyzed is from 1975 to 2016 when important institutional changes occurred. The methodology is based on a spatial panel for 59 developed and developing countries and for subsamples comprising countries on the American continent and some countries that make up Latin America and the Caribbean to visualize the sensitivity of the results in these regions. Models without spatial control, such as ordinary panel least squares (OLS), were estimated. And, models with spatial control, particularly: i) model of spatial error (SEM); ii) spatial autoregressive model (SAR); iii) Durbin's spatial model (SDM). The dependent variable is the GDP growth rate per capita and, as explanations, there are: initial GDP per capita, proxies for physical and human capital, trade flow and population growth (controls) and two indexes that measure the quality of institutions, Polity IV and Fraser Institute. The first, informs the levels of democracy and autocracy of nations, while the second indicates the economic freedom of countries. The results indicate that the economic institutions are important for the economic growth of the countries in all the sample cuts evaluated. It was also observed that the effects of political institutions were more expressive in the cases of the samples for countries in the American continent and Latin America and the Caribbean. In addition, the speed of convergence between countries increases when economic institutions are incorporated into the model.